2008
DOI: 10.1590/s0100-06832008000300038
|View full text |Cite
|
Sign up to set email alerts
|

Respostas fisiológicas da laranjeira 'Pêra' aos sistemas de manejo de cobertura permanente do solo nas entrelinhas

Abstract: A presença de plantas de cobertura permanente nas entrelinhas dos pomares pode comprometer a absorção de água e a fisiologia das laranjeiras. O objetivo deste estudo foi caracterizar as relações entre as variáveis fisiológicas das folhas das laranjeiras e o teor de água de um Argissolo Vermelho distrófico latossólico textura arenosa/média em sistemas de cobertura permanente do solo na entrelinha com gramínea "grama mato-grosso" ou "batatais" (Paspalum notatum), leguminosa amendoim forrageiro (Arachis pintoi) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
3
0
3
Order By: Relevance
“…Several studies conducted in the same area of this experiment have shown the efficiency of superficial limestone used in undisturbed soil TORMENA, 2005, AULER et al, 2008. These results have demonstrated that strip tillage treatment, in which the limestone is applied on the soil surface without incorporation, does not have negative effects on the soil's chemical properties (0-40 cm) or on the orchard's orange production (AULER et al, 2008).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Several studies conducted in the same area of this experiment have shown the efficiency of superficial limestone used in undisturbed soil TORMENA, 2005, AULER et al, 2008. These results have demonstrated that strip tillage treatment, in which the limestone is applied on the soil surface without incorporation, does not have negative effects on the soil's chemical properties (0-40 cm) or on the orchard's orange production (AULER et al, 2008).…”
Section: Introductionsupporting
confidence: 52%
“…Traditionally, soil disturbance methods have been employed because of the incorrect idea that soil disturbance is indispensable for limestone incorporation at the orchard's establishment and that the orange orchard must have a clean soil surface because permanent intercropped vegetable cover compete with the orange tree for soil water. However, results obtained in the same area TORMENA, 2005;AULER et al, 2008;FIDALSKI et al, 2008) have shown the efficiency of superficial limestone use on undisturbed soil (without incorporation). Strip tillage does not have negative effects on soil chemical properties at 0-40 cm depth (FIDALSKI ; TORMENA, 2005) nor on orange production (AULER et al, 2008).…”
Section: Carbon and Nitrogen Mineralizationmentioning
confidence: 92%
“…The evaluations were conducted after a total (Tables 5, 6 and 7), which corresponded, respectively, to soil water potentials below wilting point (-1,500 kPa) and near to field capacity (-8 kPa) which are close to the results of Fidalski et al (2008) in a similar soil under orange.…”
Section: Resultsmentioning
confidence: 89%
“…O maior valor de IHO na camada superficial arenosa está associado ao maior teor de carbono orgânico (Quadro 1). Fidalski et al (2008b) incorporaram o carbono orgânico nos ajustes das curvas de retenção de água do solo e curvas de resistência do solo à penetração, que verificaram maior θ e menor RP, refletindo em maior IHO no tratamento com gramínea (Fidalski et al, 2010). O uso e manejo desses solos com gramínea atendem a aptidão agrícola desses solos (Embrapa, 1984), que estão recobertos por pastagem em 70 % da área agrícola do noroeste do Paraná.…”
Section: Resultsunclassified
“…Essa camada é constituída por solo arenoso e com teores intermediários de carbono orgânico, que com o aumento da sua Ds eleva a RP, reduzindo abruptadamente o IHO (Figuras 2 e 3). Para reduzir os efeitos da RP nesses solos, deve-se priorizar o manejo com gramíneas para manter os teores de carbono orgânico, o maior IHO e a disponibilidade de água para as plantas (Fidalski & Tormena, 2007;Fidalski et al, 2008b;Silva et al, 2009;Fidalski et al, 2010a).…”
Section: Resultsunclassified